193k views
4 votes
9+3 + 4t + 5+3 - 2 + t =

1 Answer

4 votes

We can simplify the expression: 9+3 + 4t + 5+3 - 2 + t, by following these steps:

1. Combining like terms, we can add and subtract the terms that are not multiplied by the variable t:

9+3 + 4t + 5+3 - 2 + t = 9+3+5+3-2+4t+t = 18 + 4t + t

2.Combine the terms that are being multiplied by the variable t, like this:

18 + 4t + t = 18 + 5t

Then, after combining like terms, we get the expression:

18 + 5t

User Nikola Dimitrovski
by
5.0k points